2009
DOI: 10.1159/000245900
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factors, Angiogenesis, and Survival in Human Ileal Enterochromaffin Cell Carcinoids

Abstract: Background and Aims: Well-differentiated neuro-endocrine ileal carcinoids are composed of serotonin-producing enterochromaffin (EC) cells. Life expectancy is determined by metastatic spread to the liver because medical treatment options are still very limited. Selective inhibition of angiogenesis or lymphangiogenesis might prevent tumour growth and metastatic spread. We examined the role of the vascular endothelial growth factors (VEGFs) A, B, C, D, and their receptors (VEGFRs) 1, 2, 3 in angiogenesis and lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 114 publications
(93 reference statements)
0
23
2
2
Order By: Relevance
“…We also found a trend toward an association between higher vascularization and presence of liver metastasis, which suggests that the development of angiogenesis parallels IET growth. However, this result contrasts with a recent study [23], where the vascularization was lower in metastatic cases although not reaching statistical significance (p = 0.08). These discrepant results probably underline that the counting of vessels is heterogeneous in the different layers of the ileal wall.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also found a trend toward an association between higher vascularization and presence of liver metastasis, which suggests that the development of angiogenesis parallels IET growth. However, this result contrasts with a recent study [23], where the vascularization was lower in metastatic cases although not reaching statistical significance (p = 0.08). These discrepant results probably underline that the counting of vessels is heterogeneous in the different layers of the ileal wall.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, they are frequently aggressive and metastatic to lymph nodes and the liver and resistant to chemotherapy. Recent evidence suggested that angiogenesis is important for tumorigenesis of IET [23]. New therapeutic strategies, including antiangiogenic therapy targeting, are needed in order to treat patients with disseminated metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-A expression was similar between tumor lesions and healthy ileal mucosa. In contrast, VEGF-B and VEGF-D levels were higher in tumors than in normal mucosa (31). This might explain why several of the NET lesions in our study did not show uptake of 89 Zr-bevacizumab.…”
Section: Discussioncontrasting
confidence: 68%
“…Выполнение лимф-аденэктомии достоверно улучшает общую выживаемость. Адекватным объемом лимфо-диссекции при НЭО тонкой кишки, по мне-нию некоторых авторов, необходимо считать удаление как минимум 8 лимфатических узлов [64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: хирургическое лечениеunclassified